Resilience in Human Resource Management: How Organizations Adapt to Uncertainty and Crisis - Fitrah Sari; Silvia Iskandar; Yohan Fitriadi (International Journal of Economics and Management Research, 2025)
This study investigates the strategic role of Human Resource Management (SHRM) in building Organizational Resilience (OR), particularly through the moderating effect of Transformational Leadership (TL) and the contextual influence of organizational culture. The research addresses a pressing problem: how organizations can maintain adaptability and continuity amid persistent uncertainty and crisis. The objective is to propose and validate an integrative conceptual model linking SHRM practices, leadership behavior, and employee engagement to resilience outcomes. A qualitative exploratory case study design was employed, involving semi structured interviews with senior HR professionals and organizational leaders from multiple industries that have experienced disruption in the past five years. Thematic analysis was applied to identify patterns and validate findings through triangulation and participant feedback. The results reveal that SHRM practices such as talent agility, flexible work arrangements, and leadership development significantly enhance resilience by fostering proactive employee engagement. Furthermore, the presence of transformational leadership strengthens the implementation of these HR strategies, while organizational culture moderates the extent to which engagement translates into resilient behavior. This study contributes to the literature by offering a systemic framework that synthesizes strategic, behavioral, and contextual dimensions of resilience. The proposed model underscores the importance of aligning HR strategies with adaptive leadership and supportive culture to build organizational systems capable of sustaining performance under pressure. These findings have practical implications for HR policymakers and organizational leaders seeking to embed resilience into workforce strategies and institutional frameworks.